Checks and Balances in the Reorganization of State Institutions: A Constitutional Perspective - Aryo Akbar; Surizki Febrianto; Bagio Kadaryanto; Yusramizza Md Isa; Hyeonsoo KIM (Kosmik Hukum, 2026)
This study aims to examine the application of the principle of checks and balances within Indonesia's constitutional structure, focusing on the relations among the House of Representatives (DPR), the President, and the Supreme Court/Constitutional Court. This principle is essential to preventing the misuse of power among branches of government and to ensuring that governmental administration operates in accordance with the rule of law and constitutionalism, particularly within a presidential system such as Indonesia's. This study employs a normative legal research method, analyzing primary and secondary legal materials related to the implementation of checks and balances within Indonesia's constitutional structure. The results show that checks and balances are implemented through interaction among the executive, legislative, and judicial branches, each possessing authority to supervise and counterbalance the others, as reflected in the relationships between the legislature and executive, the executive and judiciary, and the legislature and judiciary. These dynamics are shaped by overlapping authority among state institutions, which frequently produces ambiguity in the exercise of legislative oversight and judicial review. The study concludes that optimizing checks and balances requires a clearer delineation of institutional authority, whether through statutory revision or constitutional amendment, to ensure consistent and effective oversight. These findings have practical implications for legislative drafters and constitutional policymakers in clarifying overlapping supervisory mandates and reducing institutional ambiguity.